Point-of-care microcirculation evaluated with sidestream dark field technology: agreement and comparison between sublingual and sublabial mucosa - Qu, Jinlong (Am J Transl Res, 2020)
To investigate whether sublabial mucosa is more suitable for evaluation of microcirculation than commonly used sublingual mucosa in ICU patients, we enrolled 57 adults (47 critically ill patients and 10 volunteers) at convenience from Oct 2018 to Jan 2019. Videomicroscopy images at both sublingual mucosa and sublabial mucosa were acquired at the same time in each enrollee. Qualified images were recorded for later analysis. Four video clips of the same site were comprehensively evaluated to yield one Point Of carE Microcirculation (POEM) score by blinded investigator; POEM scores at both sites were statistically analyzed for correlation and agreement. Procedure time needed to acquire qualified images was also compared. POEM scores between the two sites showed no significant difference and a statistically significant correlation (Spearman correlation coefficient 0.716, P < 0.001). The intra-class correlation coefficient was 0.866 (95% C.I. 0.774, 0.921), suggesting good to excellent consistency and agreement between the POEM scores at the two sites. The procedure time needed to acquire 4 clips of qualified images at sublingual and sublabial sites were 10.5±3.9 minutes and 7.1±3.3 minutes respectively, P < 0.001. This study indicates that point of care evaluation of microcirculation by POEM score shows good to excellent agreement between sublingual mucosa and sublabial mucosa. It is easier to acquire qualified videomicroscopy images at sublabial mucosa than at sublingual mucosa. Therefore, sublabial mucosa might be more suitable for bedside evaluation of microcirculation with handheld SDF device in ICU.